Communication Skills Success Is All a Matter of How You Say Things - Wilmore, Elaine L. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
Sometimes good teachers may mistakenly assume that teaching strategies that worked with other children will work well with all students. This paper argues that educators must listen and communicate collaboratively with the student, the family, and other educators to discover the right combination of learning styles and instructional techniques that will work for each individual child. Teachers are encouraged to engage in collaborative planning, try innovative instructional techniques, and seek out advice. Failure to do this is to risk the loss of the student's self-esteem and motivation to learn. (LMI)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communication Skills; Elementary Secondary Education; Instructional Effectiveness; Instructional Improvement; Interpersonal Relationship; Listening Skills; Teacher Student Relationship; Teaching Skills; Guides, Non-Classroom.